I don't know how to solve x^2-2x-3, could someone help with the steps, but don't give me the answer?

Guest Sep 5, 2017

#3**+2 **

x^{2} - 2x - 3 = 0

You can solve for x with the quadratic formula as Guest said, or you can factor the expression on the left side. To factor it.....you need two numbers that add to -2 and multiply to -3 .

----------

Here's an example that might help without giving away the answer.

x^{2} - 6x + 8 = 0

What two numbers add to -6 and multiply to 8 ? → -4 and -2

So, we can factor the left side like this....

(x - 4)(x - 2) = 0

Now set each factor equal to zero and solve for x .

x - 4 = 0 x - 2 = 0

x = 4 or x = 2

So x = 4 causes this expression to equal zero, and also x = 2 causes the expression to equal zero.

hectictar
Sep 5, 2017